1993
DOI: 10.1002/jcp.1041560204
|View full text |Cite
|
Sign up to set email alerts
|

Type IV collagenase(s) and TIMPs modulate endothelial cell morphogenesis in vitro

Abstract: It has been proposed that proteases are important in endothelial cell behavior. We examined the contribution of the gelatinase/type IV collagenase system in an in vitro model of endothelial differentiation. Human umbilical vein endothelial cells rapidly align and form networks of tubes when cultured on a basement membrane preparation, Matrigel. Zymograms of culture supernates demonstrate a 72-kD and a 92-kD gelatinase activity; the cells produce most of the 72-kD gelatinase, whereas the 92-kD activity is deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
153
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(162 citation statements)
references
References 47 publications
(34 reference statements)
7
153
0
2
Order By: Relevance
“…This is in agreement with studies on MMP-2 and MT1-MMP that reported that small amounts of these MMPs are essential for the onset of the morphogenetic program, whereas an excess of proteolytic activity prevents tubulogenesis and cause the reabsorption of the formed vasculature-through loss of the matrix-supporting scaffold necessary for maintaining the structure-and promotes cell invasion. 27,[32][33][34] In this respect, the need for a delicate balance between proteases and their inhibitors in each phase of the angiogenic process could provide an addition functional explanation for the presence of TIMPs in vesicles shed by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with studies on MMP-2 and MT1-MMP that reported that small amounts of these MMPs are essential for the onset of the morphogenetic program, whereas an excess of proteolytic activity prevents tubulogenesis and cause the reabsorption of the formed vasculature-through loss of the matrix-supporting scaffold necessary for maintaining the structure-and promotes cell invasion. 27,[32][33][34] In this respect, the need for a delicate balance between proteases and their inhibitors in each phase of the angiogenic process could provide an addition functional explanation for the presence of TIMPs in vesicles shed by endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have demonstrated that the gelatinases, MMP-2 and MMP-9, are involved in vascular cell migration and invasion assays. [28][29] It has been documented that MMP-2 mediates the tumorassociated angiogenesis. 30,31 Microvessel density has been found to correlate with the capacity of the tumor to metastasize, and thus is considered to be one of the most important predictors of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The TIMP-2 expression as detected by immunohistochemistry was associated with poor outcome in invasive bladder cancer patients (Grignon et al, 1996). However, several investigators have shown that the balance between MMPs and their inhibitors (TIMPs) modulated endothelial cell morphogenesis in vitro, and that TIMPs inhibited the early events in tube formation by endothelial cells on Matrigel (Schnaper et al, 1993). Therefore, MMPs and TIMPs in circulating body fluids may also contribute to the regulation of tumour metastasis, invasion and angiogesesis DeClerck et al, 1994).…”
Section: Discussionmentioning
confidence: 99%